Avaliação institucional nas escolas públicas de Fortaleza - Ce.: avanços e desafios - Rodrigues, Andrea Maria Rocha (2009)
Our investigation has as objective principal to know and to analyze the appearance of the institutional evaluation in the state public school in the municipal district of Fortaleza/CE, become pregnant by the Northeast Project, and your legitimacy level among the involved subjects. When defining me for investigating such phenomenon, I had as valid the lifted up theoretical presupposition for Ana Maria Saul. The present work has as initial concern to clear some information on the neoliberalism and the educational neoliberalism in Brazil, to understand the appearance of the institutional evaluation in the public school in the years of 1990. The purpose of that research is to do an analysis of the appearance of the institutional evaluation in the state of Ceará, trying to identify the level of involvement of the subjects and the legitimacy of the process of institutional evaluation. Basing on the conceptions of evaluation of Ana Maria Saul, with the evaluation emancipatória, I tried to investigate the importance of the institutional evaluation for a new model of democratic administration and participated, then, the school will have larger easiness of evaluating the services for her offered. To reach such objectives, we accomplished in first moment a documental analysis, leaving of the analysis of the reports published by the Secretary of Education of the State of Ceará (SEDUC), dated between 1996 and 2006. Soon after, we made a field research embracing 6 (six) state schools of the Municipal district of Fortaleza, being four that stuck to the process of the institutional evaluation since the year of 1996 four that only stuck in the last years. We used the comparative method with a quantitative and qualitative approach. As instrument of collection of data, we used forms with the following subjects: nucleus manager, teacher, employee, parents and students. For result of the research, we will proceed with a statistical analysis of the data, making possible, like this, correlations among the answers of our research and of the results of the existent data in the annual reports about institutional evaluation of SEDUC. With base in the main verifications reached along the investigation, after analysis of the data, we will have our final considerations, taking as central axis the involvement and the participation of the subjects engaged in the actions of the school for a legitimate performance in the institutional evaluation of the public school of basic education in the municipal district of Fortaleza.